2000
DOI: 10.1164/ajrccm.162.6.9805079
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Asthma in Adults in Six Canadian Communities

Abstract: We examined the prevalence, population attributable risk (PAR), and clinical characteristics of occupational asthma (OA) in a randomly selected population in six communities in Canada. Our study followed the European Community Respiratory Health Survey protocol. A randomly selected population of 18,701 (87% response rate) persons from the study communities, ranging in age from 20 to 44 yr, completed an initial questionnaire, of whom 2,974 (39% response rate) attended the laboratory and completed supplementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 14 publications
2
37
1
2
Order By: Relevance
“…Prevalence estimates of work-aggravated symptoms vary largely according to the populations studied, including 5-17% in general practice [54,55], 16-31% in tertiary asthma clinics [56,57], 20% in patients hospitalised for asthma [58], and 20-57% in population-based surveys [59][60][61][62]. These findings provide convincing evidence that workplace exposure can cause exacerbation of respiratory symptoms in a substantial proportion of subjects with pre-existing or coincident asthma.…”
mentioning
confidence: 78%
“…Prevalence estimates of work-aggravated symptoms vary largely according to the populations studied, including 5-17% in general practice [54,55], 16-31% in tertiary asthma clinics [56,57], 20% in patients hospitalised for asthma [58], and 20-57% in population-based surveys [59][60][61][62]. These findings provide convincing evidence that workplace exposure can cause exacerbation of respiratory symptoms in a substantial proportion of subjects with pre-existing or coincident asthma.…”
mentioning
confidence: 78%
“…These surveys have been restricted to individual workplaces or to groups of individuals from the same occupation [24]. More recently, population-based studies have been undertaken to estimate the prevalence of OA [25][26][27]; in addition, data from population surveys have been analysed to derive such estimates [28]. These results are helpful in providing information about the size of the problem in high-risk workplaces, although they are potentially prone to survivor bias.…”
Section: Prevalence Of Occupational Asthmamentioning
confidence: 99%
“…symptoms of wheezing, cough, dyspnoea, chest tightness that resolve after some time away from work [18,29,30]; or 2) as one or the other of combinations that include work-related respiratory symptoms, specific immunological sensitisation [31], variation in serial peak-flow measurements [32][33][34] and increased nonspecific bronchial responsiveness [7]. As uncertainty persists in the ascertainment of OA in epidemiological studies, the terms "asthma-like," "possible OA" [25] and "probable OA" [7,25] have been used to describe the syndrome. An additional source of controversy in the ascertainment of OA is that it can be defined as new-onset asthma [22] or as workaggravated asthma [35].…”
Section: Prevalence Of Occupational Asthmamentioning
confidence: 99%
“…A 2003 statement of the American Thoracic Society concluded that 15% of new-onset asthma among adults was due to occupation, but that there could be much more sickness and loss of productivity due to work-related exacerbation of existing asthma [2]. Six recent epidemiological studies conducted in five countries estimated the frequency of WEA, separate from cases of OA caused by work [3][4][5][6][7][8]. From these studies, the prevalence of WEA expressed as a percentage of working adults with asthma ranged from 14% to 24%, with a median of 19% [3,5,6,8].…”
mentioning
confidence: 99%
“…Past studies have started with asthma cases, evaluated these cases individually to determine WEA status, and then expressed the frequency of WEA as a percentage of asthma cases [3][4][5][6][7][8]. Unlike previous studies, the current investigation used a riskset approach in which ECRHS II participants with severe exacerbation of asthma were identified, and this outcome was modelled with covariates for occupational exposure to derive estimates of relative and attributable risk.…”
mentioning
confidence: 99%